O exercício gerencial do enfermeiro na estratégia saúde da família - Paes, Lucilene Gama (2013)
The current context of health in Brazil has experienced important transformations in the last years and therefore new and innovator possibilities of work must emerge. The Family Health Strategy inserts itself in this context as an important tool of rearrangement of the services in the primary care. The nurse stay before this challenge once she assumes the management of the processes of work, as well the coordination and organization of the health services. This research had as general objective: to present the meanings attributed to the interaction process by nurses in their management at the Family Health Strategy, as well as their articulation with the elaboration of a theoretical matrix in their experiences of management in the Family Health Strategy. This is a Descriptive Field Research, with qualitative approach, guided by the methodological referential respectively of the Symbolic Interactionismo and Grounded Theory. The data collection occurred during the months of March, April and May of 2012 through semi structured interviews, departing from an intensive proposal. The subjects were seven nurses, who manage the Family Health Strategy in the countryside of Rio Grande do Sul, Brazil. To analyze the data the steps of grounded theory were used: open coding, axial code and selective coding. The research obeys the ethical principles of the Res.196/96 and was approved by the Ethics Committee of the Federal University of Santa Maria. After the codification, the following categories were achieved: revealing itself as professional, living together with adversities, engaging with the organization of care, establishing the teamwork, and focusing the work on the user. The categories were organized around a central explanatory concept, with the purpose of giving the comprehension of the central phenomenon in which they are constituted: Experiencing the management of the nurse in the Family Health Strategy act: significants from the interface with the care. This phenomenon was presented through the Paradigmatic Model in order to demonstrate that the manager nurse realizes his function in the Family Health Strategy and tries to play his function putting the user as central focus of his work.